Characterization of Cellular Immune System at Different Ages in Water Buffalo (Bubalus bubalis) - Scatà, Maria Carmela; De Matteis, Giovanna; Grandoni, Francesco; Di Vuolo, Gabriele; Cappelli, Giovanna; Vecchio, Domenico (Journal of Buffalo Science, 2024)
In recent years, there has been an increased interest in understanding the immune system of the water buffalo due to the increased economic impact of this species. The study aimed to perform an in-depth evaluation of lymphoid and myeloid cells in water buffalo of different ages. We assess three multicolor panels of antibodies to evaluate by flow cytometry the percentage of the CD3+ CD4+, CD8+, and γδ T lymphocytes; CD79+ and CD21+ B lymphocytes; monocytes and cM, intM, and ncMsubsets; NK cells, granulocytes, and peripheral blood mononuclear cell (PBMC). Seventy-eight animals from three different farms were divided into three groups by age (26 in each group): 80-100 days old calves, 16-18 months old heifers, and 4-6 years old cows. Significant differences by Kruskal-Wallis test were found between age groups in the percentage of CD4+, CD8+, γδ T lymphocytes, NK cells (P=0.0001), total monocytes (P=0.0008), granulocytes (P=0.0358) and PBMC (P=0.0056). Between the farms, the adult animals showed differences in the percentage ofCD3+ (P=0.0152), CD4+ (P=0.0047), CD8+ (P=0.0019), CD4:CD8 ratio (P=0.0033) and γδ (P=0.0013) T lymphocytes; CD21+ B lymphocytes (P=0.0007);total monocytes (P=0.0100), cM and ncM subsets (P=0.0320;P=0.0252), granulocytes (P=0.0030) and PBMC (P=0.0120). The calves showed significant differences in CD79+ and CD21+ B lymphocytes (P=0.0141; P=0.0049), total monocytes (P=0.0010), cM, intM and ncM subsets (P=0.0335; P=0.0499; P=0.0065). The heifers group in CD21+ B subset (P=0.0439).In summary, this study provides the composition of lymphoid and myeloid cells in this species for the first time, highlighting large differences between age groups and between different herds.